2020
DOI: 10.1089/sur.2020.169
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Post-Operative Patients: Imaging Findings

Abstract: Background: Coronavirus 2019 in the post-operative period is challenging. Its clinical manifestations may have similarities to other septic, thoracic, or gastrointestinal post-surgical complications. Additionally, the post-operative period may be a time of increased risk for severe manifestations of COVID-19. We sought to evaluate the frequency of COVID-19 in a cohort of patients who had recently had operations who were undergoing imaging for acute symptoms and the role of chest computed tomography (CT) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
(12 reference statements)
0
17
0
1
Order By: Relevance
“…Very few studies have linked history of surgery to severe hypoxemia. Molière et al reported a risk of severe COVID-19 in the early postoperative periods (Moliere and Veillon, 2020). Indeed, the risk of nosocomial contamination of COVID-19 is greater in the immediate postoperative periods.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have linked history of surgery to severe hypoxemia. Molière et al reported a risk of severe COVID-19 in the early postoperative periods (Moliere and Veillon, 2020). Indeed, the risk of nosocomial contamination of COVID-19 is greater in the immediate postoperative periods.…”
Section: Discussionmentioning
confidence: 99%
“…This included peripheral ground glass changes or shadowing on chest radiograph or CT chest as has been reported in the literature. 9 , 10 …”
Section: Methodsmentioning
confidence: 99%
“…The oversight of not undertaking consent discussions on COVID-19 infection could have medicolegal implications, particularly in cases where non-operative management or postponement of surgery may be considered. In cases where operative management is pursued, the incidence of COVID-19 post-operatively is suggested to be as high as 17% when COVID-19 was more prevalent during the peak of the pandemic [ 9 ]. Therefore, it is a significant risk that all patients undergoing surgery should be consented for.…”
Section: Discussionmentioning
confidence: 99%